PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE TALKING STICK BERBANTUAN MEDIA QUESTION BOX DILENGKAPI LKS WORD SQUARE TERHADAP HASIL BELAJAR SISWA KELAS VIII SMP N 2 LEWA - Yorida Look, Miaty; Tamu Ina, Anita; Louise Makatita , Audrey (Universitas Cokroaminoto Palopo, 2024)
The aim of this research is to determine the effect of the Talking Stick type cooperative learning model assisted by Question Box Media complete with Word Square LKS on the learning outcomes of class VIII students at SMP Negeri 2 Lewa. This type of research is experimental research. Consisting of 2 classes, namely the control class and the experimental class. The research stages are preparation, implementation and completion. The sample in this study was 25 students from Class VIII A who served as the control class and 26 students from Class VIII B as the experimental class. . It can be concluded that the Talking Stick type cooperative learning model assisted by Question Box Media complete with Word Square LKS has a significant effect on the learning outcomes of class VIII B students, which is an experimental class at SMP Negeri 2 Lewa.